Chimpcult - (:unkn) unknown (My University, 2025)
Recently, determining if the community-specific behavioural patterns observed in apes are equivalent to the differences observed between human groups has proven crucial in understanding the origin of human cultural behaviours. In particular, knowing if the same mechanisms as in humans act to create these different patterns is controversial, because there is no experimental proof that any presumed ape cultural behaviour, notably tool use, has been socially learnt. Another question is: even if these behaviours were cultural, do they really influence apes’ all day-life, as they do for humans? In the proposed studies both questions are addressed through the use of field experiments. Field experiments are designed to bring the controlled settings of the laboratory directly in the species’ natural habitat. Several settings will be used, including the honey-trap experiment where apes attempt to retrieve inaccessible honey from a standardised hole and the artificial fruit experiment, where apes attempt to retrieve a food reward from a box. The project will seek to seed an extractive behaviour in one chimpanzee group and explore the spread of the behaviour within the group, determining if it was transmitted through individual or social learning processes. Investigating the role of a model will shed light on how social the development of tool use is. Additionally, this proposal attempts to determine the extractive knowledge of wild communities of chimpanzees throughout Uganda, in order to establish their cultural behaviour repertoire. Results will be combined with ecological studies. Finally, the project will seek to establish field experiments for social traits such as vocalisations, another side of primate cultures. Combined, the results of these studies will shed light on our own evolution, by isolating what components of human and chimpanzee cultures are common and different, and as such, which were likely present in our last common ancestor.
Keywords: culture; chimpanzees; tool use; social learning; evolution